Descartes - Bracken, Harry M. (Oneworld philosophers., 2007)
Outlining the major ideas and achievements of the great French thinker Rene Descartes, this is an introductory guide to a man whose ground-breaking theories have been rocking the status quo for over three centuries. From his birth into the brave new scientific world of Copernicus and Galileo to his demise and the unusual fate of his body, this book first presents a sound introduction to the context of Descartes's life and thought. Harry M. Bracken then draws on the words of Descartes himself to introduce the philosopher's controversial theories on the dualism of mind and body and the supremacy of the rational ideal, before providing a sharp analysis of the continuing role of Rene Descartes in our own philosophical and moral landscape.